2022
DOI: 10.1021/acs.joc.2c00819
|View full text |Cite
|
Sign up to set email alerts
|

Chlorahupetenes A–D, Four Eudesmane-Type Sesquiterpenoid Dimer Enantiomers with Two Unusual Carbon Skeletons from Chloranthus henryi Var. hupehensis

Abstract: (+)- and (−)-Chlorahupetenes A (1a and 1b), B (2a and 2b), C (3a and 3b), and D (4a and 4b), four unique enantiomeric pairs of eudesmane-type sesquiterpenoid dimers with two new carbon skeletons, were isolated from the aerial parts of Chloranthus henryi var. hupehensis. Compounds 1 and 2 possess an unprecedented 6/6/5/6/6 pentacyclic carbon skeleton with a new dimerization pattern of two eudesmane-type sesquiterpenoids. Compounds 3 and 4, which are fused with two eudesmane-type sesquiterpenoids via an unpreced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The results showed that the experimental and calculated spectra for the (4 S ,5 R ,10 R ) ‐ 10 were in good agreement. [ 5‐6 ] Accordingly, the structure of 10 was established as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results showed that the experimental and calculated spectra for the (4 S ,5 R ,10 R ) ‐ 10 were in good agreement. [ 5‐6 ] Accordingly, the structure of 10 was established as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The results (Figure 5D) showed that the calculated ECD curve was consistent with the experimental spectrum, which confirmed the above relative structure and assignment of the 1 S ,5 S ,10 S absolute configuration of 11 . [ 5‐6 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…hupehensis , have undescribed polycyclic skeletons. 15 Possible biosynthetic routes to the chlorahupetenes have been presented. It is proposed that the biosynthetic pathways to the polycyclic abietane diterpenoid dimers biseupyiheoid A 20 and bisfischoid C 21 , from Euphorbia fischeriana , involve intramolecular Diels–Alder cycloadditions with different coupling patterns.…”
mentioning
confidence: 99%